Solve the following quadratic equation using square roots:  −9+(x−3)2−4=−4

1 answer

−9+(x−3)2−4=−4 can be rewritten as (x-3)^2 -4 = 0.

To solve this quadratic equation, we can isolate (x-3)^2 by adding 4 to both sides: (x-3)^2 = 4.

Next, we take the square root of both sides to eliminate the square: x-3 = ±2.

Now, we can solve for x by adding 3 to both sides: x = 3±2.

Therefore, the solutions to the quadratic equation are x = 5 and x = 1.
Similar Questions
  1. . Find the zeros of the quadratic equation y=6x2+13x+5. You may use any of the following methods: factoring, square roots,
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Solve the quadratic equation below using square roots. (x − 4)^2 = 25A) {-1, 9} B) {-2, 6} C) {-√29, √29} D) {-3, 7}
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions